Social Media and entrepreneurship, which relationship? An empirical study among students of El Bayadh University Centre - Hadjer Derdar; Amina Moulai (Journal of North African Economies, 2025)
The virtual world has recently proven its intrinsic role in the business world, as it has become substantial in establishing projects and following their development. This study aimed to shed light on the impact of social media platforms in creating the entrepreneurial intention for students in terms of perceived desirability and perceived feasibility. Based on the case study approach, we established an E-questionnaire directed to a sample of 170 students at the University Centre in El Bayadh state. According to confirmatory analysis method, the study reached a set of results, the most important of which are: There is a statistically significant effect of social media on both the desire and the perceived feasibility in creating intention and motivating students to establish their projects due to its useful features and policies.